Relationship of Involvement in Business Capital Loans with Family Financial Literacy in Karangsoko Village, Trenggalek District, Trenggalek Regency - Sari, Adelia Jihan Tiara; Supriyono, Supriyono; Zulkarnain, Zulkarnain (Universitas Negeri Malang, 2024)
Family financial literacy is knowledge about good financial management that is useful in the long term and is applied in economic activities (Zidni & Fitanto, 2022). One of the factors that influences a person's level of financial literacy is their involvement in business capital loans. This research aims to determine the relationship between involvement in business capital loans and family financial literacy. The design of this research is correlational using sampling techniques snowball sampling. The research subjects were the people of Karangsoko Village, Trenggalek District, Trenggalek Regency who were involved in business capital loans totaling 50 respondents. This research instrument uses a questionnaire with a Likert Scale. This research uses Spearman rank correlation analysis with the results of the analysis showing that the correlation coefficient value is 0.274 so it can be said to be positively related, while the results of the significance value are 0.054 > 0.05 so it can be said to be not significant. Keywords: Business Capital Loans; Family Financial Literacy